The Icatibant Outcome Survey: experience of hereditary angioedema management from six European countries. (1st June 2017) - Caballero, T.; Aberer, W.; Longhurst, H.J.; Maurer, M.; Zanichelli, A.; Perrin, A.; Bouillet, L.; Andresen, I.
Abstract: Background: Hereditary angioedema (HAE) due to C1‐inhibitor deficiency (C1‐INH‐HAE) is a rare, potentially fatal, bradykinin‐mediated disease. Icatibant is a bradykinin B2 receptor antagonist originally approved in 2008 in the European Union and 2011 in the United States as an acute therapy option for HAE attacks in adults. Objective: To compare demographics, disease characteristics and treatment outcomes of icatibant‐treated HAE attacks in patients with C1‐INH‐HAE enrolled in the Icatibant Outcome Survey across six European countries: Austria, France, Germany, Italy, Spain and the UK. Methods: The Icatibant Outcome Survey [IOS; Shire, Zug, Switzerland (NCT01034969)] is an international observational study monitoring the safety and effectiveness of icatibant. Descriptive, retrospective analyses compared IOS country data derived during July 2009–April 2015. Results: Overall, 481 patients with C1‐INH‐HAE provided demographic data. A significant difference across countries in age at onset ( P = 0.003) and baseline attack frequency ( P < 0.001) was found although no significant differences were found with respect to gender (majority female; P = 0.109), age at diagnosis ( P = 0.182) or delay in diagnosis ( P = 0.059). Icatibant was used to treat 1893 attacks in 325 patients with majority self‐administration in all countries. Overall, significant differences (all P < 0.001) were found across countries in time to treatment [median 1.8 h; median range: 0.0 (Germany–Austria) to 4.4 (France) h], time to resolution [median 6.5 h; median range: 3 (Germany–Austria) to 12 (France) h] and attack duration [median 10.5 h; median range: 3.1 (Germany–Austria) to 18.5 (France) h]. Conclusion: These data form the first European cross‐country comparison of disease characteristics and icatibant use in patients with C1‐INH‐HAE who are enrolled in IOS. International variation in icatibant practice and treatment outcomes across the six European countries assessed highlight the need to further investigate the range of country‐specific parameters driving regional variations in icatibant use.